Pelatihan Pijat Bayi Untuk Kondisi Sembelit Di Posyandu Balita Abadi Sejahtera - Shella Dhika Rahmawati; Ni Kadek Krisna Dwi Patrisia; Almita Ratu Rifanda; Sofia Mardiana; Friesca Persityara Agatha; Aulia Ayu Kusuma (Pusat Riset dan Inovasi Nasional, 2023)
Constipation is a digestive problem that can be experienced by anyone, both parents and children. When it occurs in children, constipation which causes pain in the stomach will certainly interfere with their daily activities. There are various causes of constipation in children, ranging from cow's milk allergies, dehydration, to poor diet. Based on the data obtained, there were 2 toddlers with stomach complaints of constipation. Some parents underestimate constipation in toddlers and don't know how to reduce constipation. Based on these data, it is necessary to carry out community service